2022
DOI: 10.4102/hsag.v27i0.1775
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with smoking and transitioning to nyaope injection amongst women in the City of Tshwane Municipality: A self-report by women

Abstract: Background: Substance use disorder has emerged as a key health and social challenge in South Africa (SA). It is projected that about 15% of South African youth, especially young women are prone to engage in drug use and the prospects of coming into contact with nyaope, a highly addictive drug, are higher. Nyaope is mainly smoked, but the prevalence of injecting it is increasing in most regions.Aim: This study aimed to explore and describe the perception of women, who use nyaope, about the factors contributing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…9 There is currently more data about crime associated with the use of Nyaope 10 , 11 than on the cooperation between the police and communities in which Nyaope is openly used, cheap and easily accessible. 3 , 22 The distress felt by communities at the insurmountable problem of Nyoape use and the impunity of dealers has led them to find their own solutions, including community assaults and vigilantism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 There is currently more data about crime associated with the use of Nyaope 10 , 11 than on the cooperation between the police and communities in which Nyaope is openly used, cheap and easily accessible. 3 , 22 The distress felt by communities at the insurmountable problem of Nyoape use and the impunity of dealers has led them to find their own solutions, including community assaults and vigilantism.…”
Section: Discussionmentioning
confidence: 99%
“… 21 There is also mounting evidence of poor social services in general, which is consistent with our data analysis. 3 , 4 , 5 , 6 , 7 , 17 , 18 , 19 , 20 , 21 , 22 The failure of health and social services to tackle the problem contributes, in turn, to Nyaope-related family and community distress and dysfunctional solutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without the availability of widespread interventions, injection drug use has continued to increase in South Africa with a prevalence of 0.6% in a population-based survey in 2012 with 0.2% reporting Whoonga use [36]. More recent studies estimate that up to 15% of South African youth engage in drug use [16,37]. However, small pilot studies have shown high retention rates, opiate reduction, and improvement in mental health in individuals accessing methadone…”
Section: Discussionmentioning
confidence: 99%
“…This drug cocktail is commonly referred to as nyaope [17,[34][35][36]39,41,43,44,46,47,52,54,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72]. According to prior media reports and studies, this drug cocktail has also been referred to by other names, including whoonga [38,39,41,46,49,52,54,59,[62][63][64]68,70,71,73], wunga [46,62,64], plazana [53], kataza [40,52,68],...…”
Section: Nyaope-a Highly Addictive Novel Psychoactive Drug In South A...mentioning
confidence: 99%